Fragment response of unreinforced concrete masonry walls subjected to blast loading. Issue 2 (June 2022) - Hatfield, John E; Pezzola, Genevieve L; Walker, Robert E; Stephens, Catherine S; Davidson, James S
Very few methods are available for predicting the secondary fragment velocity and secondary fragment production of ungrouted and nonreinforced concrete masonry unit (UGNR CMU) walls when subjected to blast loading. Existing approaches often require large computational resources or fail to predict secondary fragment velocity accurately. This paper presents an engineering-level analysis methodology that can be rapidly implemented to predict the velocity of fragments from UGNR CMU walls subjected to blast loading. The theoretical background and need for the methodology are discussed. Results from the analytical methodology are compared to results from two full-scale experiments and four quarter-scale experiments. A strong correlation is demonstrated between the experimental results and the analytical methodology.